Infants of the Spring (1932): Cutting across the Stage of Harlem’s Black Bohemia - Elisa Cecchinato (Transatlantica)
Based on an analysis of the novel Infants of the Spring (1932), this article explores the circulation and metamorphoses of Black and queer cultural identities in the urban space of Harlem (New York) during the 1920s. In this roman à clef, Black American writer and editor Wallace Thurman revisited the experience of the Black bohemia. He did so focusing on the so-called “Niggeratti Manor,” a residence where some of the young Black artists of the Harlem Renaissance lived. At the time, New York was still organized along racially segregated lines and various factors were shaping the uptown neighborhood: the migration of Black Americans from the South to the North of the United States; the urban reforms that aimed to organize this migration; and the political, intellectual, and artistic production that accompanied the Black emancipation struggles. In addition, during this period, which was also that of Prohibition, white queer men and women patronized the neighborhood. On the one hand, Harlem was a fairly welcoming area for gay and lesbian people. On the other hand, it provided access to an entertainment world in which performance and camp were central. This article discusses how, using the metaphor of theater, and specifically the highly racially codified genre of the minstrel show, Infants of the Spring depicts male, Black, and queer identities in the modern urban landscape. Thurman’s novel interrogates the formation and circulation of these identities through the lens of the multiple relationships that Black artists had with white men, artists, and lovers, as well as with Black artists, intellectuals, and reformers.